The Anti-inflammatory Compound Candesartan Cilexetil Improves Neurological Outcomes in a Mouse Model of Neonatal Hypoxia - Quinlan, Sean; Merino-Serrais, Paula; Di Grande, Alessandra; Dussmann, Heiko; Prehn, Jochen H. M.; Ní Chonghaile, Tríona; Henshall, David C.; Jimenez-Mateos, Eva M. (Frontiers in Immunology, 2019)
Recent studies suggest that even mild hypoxia-induced neonatal seizures can trigger an acute neuroinflammatory response leading to long-lasting changes to brain excitability and associated cognitive and behavioral deficits. The cellular elements and signaling pathways underlying neuroinflammation in this setting remain incompletely understood but could yield novel therapeutic targets. Here we show that brief global hypoxia-induced neonatal seizures in mice result in short-lasting cytokine production as well as selective expansion of the brain microglia population and long-lasting changes to the neuronal structure of pyramidal neurons in the hippocampus. Treatment of neonatal mice after hypoxia-seizures with the novel anti-inflammatory compound cardensatan cilexetil suppressed acute seizure-damage and mitigated later-life aggravated seizure responses and hippocampus-dependent learning deficits. Together, these findings improve our understanding of the effects of neonatal seizures and identify potentially novel treatments to protect against short and long-lasting harmful effects.